Měrćin -Njechorński and His Writing in the Sokołske Listy Magazine - Kijová, Kinga (Lidé města, 2008)
Měrćin Nowak–Njechorński was with no doubt one of the most important authors publishing in the Sokołske listy magazine. In fact, in some periods, he was the author of almost the entire content of this monthly. The activity of Měrćin -Njechorński as editor of this magazine in the years 1928 – 1933 isNowak covered in this article. In his writings, the Sorbian activist tackled a variety of issues: social, political and national. He actively promoted the ideas of Sokol and considerably contributed to the formation of patriotic feelings in the generation of Młodoserbs, the “young Sorbians”. His work strongly influenced the shape of the Sorbian nation in the period between the wars as well as in the post-war era.